2021
DOI: 10.1371/journal.pone.0258591
|View full text |Cite
|
Sign up to set email alerts
|

Can differences in innovativeness between European cross-border regions be explained by factors impeding cross-border business interaction?

Abstract: Business interaction is important for innovation performance but may be challenging in cross-border regions. The objective of this research was to investigate the relation between factors that define cross-border business interaction and innovativeness. From the cross-border regional innovation systems literature, we operationalized thirty-five factors which potentially influence cross-border business interaction; these factors concern availability of science and knowledge bases, socio-cultural proximity, acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Basboga's exploration of border openness and cross-border cooperation's impact on regional growth in European regions underscores the role of cross-border activities in fostering economic development (Basboga 2020). Neuberger et al have scrutinized the relationship between regional innovativeness and location factors, including proximity to borders (Neuberger et al 2021). While our study confirms the importance of border proximity, it also emphasizes that it cannot be the sole determinant.…”
Section: Discussionsupporting
confidence: 56%
“…Basboga's exploration of border openness and cross-border cooperation's impact on regional growth in European regions underscores the role of cross-border activities in fostering economic development (Basboga 2020). Neuberger et al have scrutinized the relationship between regional innovativeness and location factors, including proximity to borders (Neuberger et al 2021). While our study confirms the importance of border proximity, it also emphasizes that it cannot be the sole determinant.…”
Section: Discussionsupporting
confidence: 56%
“…Figure 3-1 Conceptual framework to investigate the influence of the cross-border innovation environment on specific stages of the innovation process (adopted from Tzokas, Hultink, and Hart 2004;Galanakis 2006;Lundquist and Trippl 2013;Hekkert et al 2007;Trippl 2010;Spendrup and Fernqvist 2019;Bansal and Grewatsch 2020;Neuberger et al 2021) In the first layer, we distinguish four stages of the innovation process as a funnel, i.e. idea generation, concept development, product development, and market entrance (i.e.…”
Section: Conceptual Framework: Cross-border Innovation Environmentmentioning
confidence: 99%
“…Klerkx and Leeuwis 2008). For example, cooperation is important for innovation development, but prior research showed that SMEs struggle to develop strong networks even in a national context (Tödtling and Kaufmann 2002), which implies additional barriers arise in a cross-border context (Neuberger et al 2021). Based on earlier studies of Knockaert, Vandenbroucke, and Huyghe (2013), Faure et al (2019), and van den Broek, Benneworth, and Rutten (2019), we argue that SMEs have different needs to develop their business in cross-border regions and to establish cross-border networks, compared to national operating SMEs.…”
Section: Introductionmentioning
confidence: 99%